2017
DOI: 10.1200/jco.2016.71.0806
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications of Genetic Mutations in Myelodysplastic Syndrome

Abstract: Myelodysplastic syndrome (MDS) is clonal disorder characterized by ineffective hematopoiesis and a tendency to evolve into acute myeloid leukemia (AML). Genetic studies have enabled the identification of a set of recurrently mutated genes central to the pathogenesis of MDS, which can be organized into a limited number of cellular processes, including RNA splicing, epigenetic and traditional transcriptional regulation, and signal transduction. The sequential accumulation of mutations drives disease evolution fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
89
1
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(103 citation statements)
references
References 70 publications
4
89
1
9
Order By: Relevance
“…MDS arises from abnormal hematopoietic stem cells, with detectable somatic mutations in virtually all patients [2,3], and recent studies also showed that germline mutations are found in a portion of MDS [4,5]. These results clearly demonstrate that the genomic status is highly influential on clinical features of MDS [3].…”
Section: Introductionsupporting
confidence: 58%
“…MDS arises from abnormal hematopoietic stem cells, with detectable somatic mutations in virtually all patients [2,3], and recent studies also showed that germline mutations are found in a portion of MDS [4,5]. These results clearly demonstrate that the genomic status is highly influential on clinical features of MDS [3].…”
Section: Introductionsupporting
confidence: 58%
“…Classification of frequently mutated genes in MDS and CMML according to their functional category (modified from Kennedy & Ebert, ; Kennedy & Ebert, ).…”
Section: Mutational Landscape Of Mds and Cmmlmentioning
confidence: 99%
“…Driver genes in MDS and CMML, which are common among the spectrum of myeloid malignancies, affect specific cellular processes and can be categorized according to their function (Greenberg et al, 2017;Kennedy & Ebert, 2017;McClure et al, 2018) (Fig 1).…”
Section: Mutational Landscape Of Mds and Cmmlmentioning
confidence: 99%
See 2 more Smart Citations